Exploring the relationship between patient-relevant outcomes and Alzheimer’s disease progression assessed using the clinical dementia rating scale: a systematic literature review - Cummings, Jeffrey; Hahn-Pedersen, Julie Hviid; Eichinger, Christian Stefan; Freeman, Caroline; Clark, Alice; Tarazona, Luis Rafael Solís; Lanctôt, Krista (Frontiers in Neurology, 2023)
Background People with Alzheimer’s disease (AD) have difficulties in performing activities of daily living (ADLs) as the disease progresses, commonly experience neuropsychiatric symptoms (NPS), and often have comorbidities such as cardiovascular disease. These factors all contribute to a requirement for care and considerable healthcare costs in AD. The Clinical Dementia Rating (CDR) scale is a widely used measure of dementia staging, but the correlations between scores on this scale and patient-/care partner-relevant outcomes have not been characterized fully. We conducted a systematic literature review to address this evidence gap. Methods Embase, MEDLINE, and the Cochrane Library were searched September 13, 2022, to identify published studies (no restriction by date or country) in populations with mild cognitive impairment due to AD or AD dementia. Studies of interest reported data on the relationships between CDR Global or CDR–Sum of Boxes (CDR-SB) scores and outcomes including NPS, comorbidities, ADLs, nursing home placement, healthcare costs, and resource use. Results Overall, 58 studies met the inclusion criteria (42 focusing on comorbidities, 14 on ADLs or dependence, five on nursing home placement, and six on economic outcomes). CDR/CDR-SB scores were correlated with the frequency of multiple NPS and with total scores on the Neuropsychiatric Inventory. For cardiovascular comorbidities, no single risk factor was consistently linked to AD progression. Increasing CDR/CDR-SB scores were correlated with decline in multiple different measures of ADLs and were also associated with nursing home placement and increasing costs of care. Conclusion NPS, ADLs, and costs of care are clearly linked to AD progression, as measured using CDR Global or CDR-SB scores, from the earliest stages of disease. This indicates that scores derived from the CDR are a meaningful way to describe the severity and burden of AD for patients and care partners across disease stages.